Education and Fertility in Urban Poor Communities in Accra, Ghana - Amarh, E.A. (University of Ghana, 2014)
This study examined the relationship between female education and fertility in urban poor communities, namely James Town, Usher Town and Agbogboloshie. Using the second round of the 2011 Urban and Health Project data conducted by the Regional Institute for Population Studies (RIPS), fertility levels for different educational categories were estimated. The unit of analysis for the study was women in their reproductive ages (15–49). A sample of five hundred and forty three (543) women in their reproductive ages was used for the study. Children ever born was used to measure fertility. Three methods of analysis, namely univariate, bivariate and multivariate were used for the study. The mean age of the women was 30.0 years. With regards to their highest level of educational attainment , more than half of the respondents (70.9%) had basic education (primary and middle/JSS) level of education and about one fifth (20.8%) of the women had secondary and higher level of education. Bivariate analysis showed that women with secondary and higher education had the lowest MCEB (0.81) compared to women with no education (2.96). The MCEB tends to decrease as the level of education of the women increases. The multivariate analysis revealed that age and marital status were the most significant variables influencing fertility behaviour in urban poor communities while the intermediate variables (contraceptive use and abortion experiences) as well as the other variables (locality, religion, occupation, ethnicity and household wealth) were not significant. Based on the findings of the study it is therefore recommended that, the Ministry of Education, non-governmental organizations (NGOs) and other stakeholders must make efforts to increase the levels of female educational attainment in order to reduce their risk of exposure to childbearing.
Thesis (M.A) - University of Ghana, 2014
Keywords: EDUCATION; FERTILITY; URBAN POOR COMMUNITIES; ACCRA, GHANA